Preparation of NiCoFe-hydroxide/polyaniline composite for enhanced-performance supercapacitors. Issue 8 (August 2019) - Liu, Lu; Hu, Xi; Zeng, Hong-Yan; Yi, Mo-Yu; Shen, Shi-Gen; Xu, Sheng; Cao, Xi; Du, Jin-Ze
Abstract: Ternary NiCoFe layer hydroxides with different Ni/Co/Fe molar ratios were prepared using simple urea method. By finely tuning Ni/Co/Fe molar ratio, the optimized hydroxide (LDH2.0 ), a Ni/Co/Fe molar ratio of 2.0/1.0/1.0, provided high specific capacitance (408 F g −1 at 2.0 A g −1 ) and good stability (90.9% retention over 1000 cycles) due to maximum crystallinity (91.35% crystallinity) and specific surface area (160 m 2  g −1 ). In order to further improve the electrochemical performances, the LDH2.0 was made into a composite (LDH/PANI) with polyaniline (PANI) via in situ polymerization of aniline monomer. The LDH/PANI composite had a much higher specific capacitance (717 F g −1 at 2.0 A g −1 ) compared with the LDH2.0, and a significant improvement of cycleability (84.7% retention over 1000 cycles). The results indicated that the LDH/PANI had a synergistic effect of both components due to the complementary properties, which guaranteed a good electric contact and consequently increased the specific capacitance. These provided a new approach for designing organic-inorganic composite materials with potential application in supercapacitors.